Sustainable quality of life criteria for Ledang National Park community: fuzzy approach - Tarmudi, Zamali; Ahmad, Shamsatun Nahar; Harun, Nurul ‘Aini; Arunah, Nor Siti Khadijah (UiTM Cawangan Johor, 2021)
Recently, there is a rising concern among researcher regarding the issue of sustainable criteria for quality of life (QoL). As it gains more interest, the issue becomes highly debated worldwide especially with regards to the national park community area. The aim of this study is to assess the identified sustainable criteria for QoL, particularly for the surrounding community of Ledang National Park (LNP) using the fuzzy Analytical Network Process (LNP).